Traditions and Rituals of the Naqshbandiyah Order in Pondok Persulukan Darul Aman Purbaganal, Sosopan - Armyn Hasibuan; Muzakkir; Abrar M. Dawud Faza (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
This aims of this study is to find out Traditions and Rituals of the Naqshbandiyah Order of Pondok Persulukan Darul Aman Purbaganal, Sosopan. This study use qualitative research design. The result of this study shows that the tradition starts from surrendering oneself to the sheikh or murshid then bathing and dikapi, accepting the tarekat, taking allegiance and others full of traditions and rituals. By staying at Pondok Persulukan, you will be able to follow the traditions, including Suluk customs to completion, genealogy and diplomas. At the Darul Aman Islamic Boarding School, the Ancient Naqsyabandiyah Order, Ganal Sosopan, North Padang Lawas, it was also a tradition to perform ablution, maintain self-purity, perform fardu prayers in congregation during seclusion or not, dhikr, tawajuh, halaqah talaqi, and rabithah.which of course have their own rituals. The results of the tradition at Pondok Persulukan are the adab tradition of respecting the murshid and the tradition of genealogy and diplomas.In relevating the traditions and rituals inherent in the substance of Suluk with Islamic teachings in contemporary life, there are changes found in Pondok Persulukan Darul Aman Naqsyabandiyah North Padang Lawas, especially in traditional and ritual processes. The goal is to accelerate the achievement of increasing understanding and in building personal character and noble character for all tarekat practice students, the existence of linkages in Suluk activities to fulfill religious spiritual needs in society and the existence of the Suluk tradition in the development of non-formal Islamic education.